(3x^2+4)^2+(3x^2-4)^2-2(5-3x^2)(5+3x^2)=

(3x^2+4)^2+(3x^2-4)^2-2(5-3x^2)(5+3x^2)=
Гость
Ответ(ы) на вопрос:
Гость
(3x^2+4)^2+(3x^2-4)^2-2(5-3x^2)(5+3x^2)=9x^4+24x^2+16+9x^4-24x^2+16-2*(5-3x^2)*(5+3x^2)=18x^4+16+16-2*(5-3x^2)*(5+3x^2)=18x^4+32-(10-6x^2)*(5+3x^2)=18x^4+32-50+18x^4=18x^4-18+18x^4=36x^4-18
Гость
[latex](3x^2+4)^2+(3x^2-4)^2-2(5-3x^2)(5+3x^2)= \\= 9x^4+24x^2+16+9x^4-24x^2+16-2(25-9x^4)= \\ = 18x^4+32-50+18x^4=36x^4-18=18(2x^4-1)[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы